Methodology for the determination of blending proportions of raw waters and optimum dosage of treatment chemicals - Adhityan Appan (2008)
The main objective of this study is to arrive at the most appropriate mixing combinations of raw waters from these three sources sucj that the cost of treatment chemicals is a minimum.